Pichia pastoris-expressed dengue 2 envelope forms virus-like particles without pre-membrane protein and induces high titer neutralizing antibodies. - Shailendra Mani (Public Library of Science (PLoS), 2013)
Dengue is a mosquito-borne viral disease with a global prevalence. It is caused by four closely-related dengue viruses (DENVs 1-4). A dengue vaccine that can protect against all four viruses is an unmet public health need. Live attenuated vaccine development efforts have encountered unexpected interactions between the vaccine viruses, raising safety concerns. This has emphasized the need to explore non-replicating dengue vaccine options. Virus-like particles (VLPs) which can elicit robust immunity in the absence of infection offer potential promise for the development of non-replicating dengue vaccine alternatives. We have used the methylotrophic yeast Pichia pastoris to develop DENV envelope (E) protein-based VLPs. We designed a synthetic codon-optimized gene, encoding the N-terminal 395 amino acid residues of the DENV-2 E protein. It also included 5' pre-membrane-derived signal peptide-encoding sequences to ensure proper translational processing, and 3' 6× His tag-encoding sequences to facilitate purification of the expressed protein. This gene was integrated into the genome of P. pastoris host and expressed under the alcohol oxidase 1 promoter by methanol induction. Recombinant DENV-2 protein, which was present in the insoluble membrane fraction, was extracted and purified using Ni(2+)-affinity chromatography under denaturing conditions. Amino terminal sequencing and detection of glycosylation indicated that DENV-2 E had undergone proper post-translational processing. Electron microscopy revealed the presence of discrete VLPs in the purified protein preparation after dialysis. The E protein present in these VLPs was recognized by two different conformation-sensitive monoclonal antibodies. Low doses of DENV-2 E VLPs formulated in alum were immunogenic in inbred and outbred mice eliciting virus neutralizing titers >1,1200 in flow cytometry based assays and protected AG129 mice against lethal challenge (p<0.05). The formation of immunogenic DENV-2 E VLPs in the absence of pre-membrane protein highlights the potential of P. pastoris in developing non-replicating, safe, efficacious and affordable dengue vaccine.